2019
DOI: 10.3839/jabc.2019.007
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion ofGentiana scabraBunge increases the anti-inflammatory effect in RAW 264.7 cells via MAP kinases and NF-κB pathway

Abstract: Mitogen-activated protein (MAP) kinases play an important role in cell growth and differentiation, as well as the modulation of proinflammatory cytokines. The objective of this study was to examine the increase in the anti-inflammatory effect of Gentiana scabra Bunge (GSB), due to bioconversion with the Aspergillus kawachii crude enzyme, via inhibition of the NF-κB signaling and MAP kinase pathways in RAW 264.7 cells. The expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 in RAW 264.7 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…FE and BFE were obtained from the National Development Institute of Korean Medicine. The extraction process was performed as previously described [ 23 , 24 ]. Briefly, A. quinata was refluxed with 70% MeOH, filtered through filter paper, concentrated using a rotary evaporator, bioconverted using the enzyme isolated from the soybean paste fungi Aspergillus kawachii , and then fractionated sequentially in butanol (BuOH) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…FE and BFE were obtained from the National Development Institute of Korean Medicine. The extraction process was performed as previously described [ 23 , 24 ]. Briefly, A. quinata was refluxed with 70% MeOH, filtered through filter paper, concentrated using a rotary evaporator, bioconverted using the enzyme isolated from the soybean paste fungi Aspergillus kawachii , and then fractionated sequentially in butanol (BuOH) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then, previous researches have shown that Rheum palmatum L. and Radix Aucklandiae could inhibit cancer cell metastasis and induce apoptosis by regulating the expression of apoptosis-related proteins 6 , 7 . Reports in the literatures indicated that Gentiana scabra Bunge and Citrus aurantium L. have been commonly applied on diseases for their anti-inflammatory, anti-tumor and anti-oxidant properties 8 , 9 . For PRGRC, due to its complex composition, the molecular mechanism on gastric cancer was not yet clear.…”
Section: Introductionmentioning
confidence: 99%